2016
DOI: 10.5897/ajb2015.15060
|View full text |Cite
|
Sign up to set email alerts
|

Response of chickpea (Cicer arietinum L.) to inoculation with native and exotic Mesorhizobium strains in Southern Ethiopia

Abstract: A series of pot and two consecutive crop-year field experiments were conducted from 2011 to 2012 in Southern Ethiopia to determine the effectiveness of Mesorhizobium strains on two cultivars of chickpea (Shasho and Nattoli). The eight treatments included: Six rhizobial inoculants, the four best indigenous strains (Cp8, Cp41, Cp97 and Cp105); CpNSTC (National Soils Testing Center inoculant); and CpSK (Canadian inoculant), Nitrogen fertilizer and a control. The results from the field and pot experiments indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Similar results were obtained by Wani et al (2007). Tena et al (2016) also reported that inoculation had a pronounced effect on grain yield of chick pea.…”
Section: Grain Yieldsupporting
confidence: 79%
“…Similar results were obtained by Wani et al (2007). Tena et al (2016) also reported that inoculation had a pronounced effect on grain yield of chick pea.…”
Section: Grain Yieldsupporting
confidence: 79%
“…In Africa, Ethiopia ranks first in chickpea cultivation in terms of area and production (Shiferaw et al 2009). However, the national average production is only 1.7 ton ha −1 (Shiferaw et al 2009;Tena et al 2016a;Wolde-meskel et al 2018), far below the potential yield of 5.0 ton ha −1 (Giller 2001;Keneni et al 2011). Like elsewhere in sub-Saharan Africa, soil fertility and high fertiliser costs constrain production in Ethiopia, with smallholder farmers usually growing legumes without additional nutrients (Wolde-meskel et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is surprisingly little literature on differential symbiotic effectiveness of diverse Mesorhizobium strains in chickpea, probably as a result of the crop's perceived symbiotic specificity. The few existing studies suggest that diverse Mesorhizobium strains can differ in symbiotic performance (Aouani et al 1997(Aouani et al , 2001Ben Romdhane et al 2008;Elias and Herridge 2015;Tena et al 2016a), while others demonstrate differences in nitrogen fixation among chickpea cultivars (Beck 1992). The occurrence of so called G L x G R interaction in chickpea is even less well studied, with apparently only a single published study that used two unidentified strains and eight crop varieties to show some evidence of interaction (Beck 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Chickpea Mesorhizobium strain CP-41 that was selected based on its ability to enhance nodulation and grain yield under wide ecological condition (Funga et al, 2016;Tena et al, 2016) was obtained from MBI (Menagesha Biotechnology Industry). Seed inoculation was performed before sowing using the procedure developed by Fatima et al (2007).…”
Section: Experimental Set-upmentioning
confidence: 99%